Pengaruh Pengetahuan dan Pemahaman Peraturan Perpajakan, Penghindaran Pajak dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak - Davidya Febri; Tri Sulistyani (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
The purpose of this study was to determine the effect of knowledge and understanding of taxation regulations, tax avoidance and taxation sanctions simultaneously and partially on taxpayer compliance. To find out the difference in knowledge and understanding of taxation regulations, tax avoidance, taxation and compliance sanctions on private taxpayers of private employees with ASN's personal taxpayers. In this study using the population of all individual taxpayers registered in the Tegal City KPP with a sample of 100 respondents. The sampling technique using simple random sampling. Methods of data collection by distributing questionnaires. The data is processed using SPSS program version 23. The results of this study conclude that the first hypothesis is that there is the influence of knowledge and understanding of tax regulations, tax avoidance and taxation sanctions simultaneously on taxpayer compliance with a significant value of 0,000. The second hypothesis is that there is an influence of knowledge and understanding of taxation regulation partially to taxpayer compliance with the significant value equal to 0,011. The third hypothesis is that there is no partial tax avoidance effect on taxpayer compliance with a significant value of 0.069. The fourth hypothesis is that there is a partial effect of taxation sanctions on taxpayer compliance with a significant value of 0.030. The fifth hypothesis is that there are differences in knowledge and understanding of taxation regulations, tax evasion, tax sanctions and compliance with private taxpayers private employees with taxpayers personal ASN. While for both groups of taxpayers both private and ASN employees do not differ or there is no difference in preferences on tax sanctions.